If it's not what You are looking for type in the equation solver your own equation and let us solve it.
16(x+3)=8(x-5)-5(x+4)-9
We move all terms to the left:
16(x+3)-(8(x-5)-5(x+4)-9)=0
We multiply parentheses
16x-(8(x-5)-5(x+4)-9)+48=0
We calculate terms in parentheses: -(8(x-5)-5(x+4)-9), so:We get rid of parentheses
8(x-5)-5(x+4)-9
We multiply parentheses
8x-5x-40-20-9
We add all the numbers together, and all the variables
3x-69
Back to the equation:
-(3x-69)
16x-3x+69+48=0
We add all the numbers together, and all the variables
13x+117=0
We move all terms containing x to the left, all other terms to the right
13x=-117
x=-117/13
x=-9
| -7y+3(y-6)=-14 | | -12=-8z+18 | | -15+3x/7x=-43 | | -7y+3(y-6=-14 | | 25x=40+x | | 4=174-u | | -6x+2(x+6)=20 | | (4x+6)°+(11x-6)°=180 | | 2x^2(6x-8)+4=39 | | 286=-x+224 | | 4+2(z−7)=−3(3+z)+4z−2 | | -3=2/3(-1)+x | | 18x+3=15x+2 | | 8(w-4)-4w=-16 | | (5r+20)/15=(4r-24)/4 | | m-6/7=8 | | 12=4+4j | | -11x+10=13x-2 | | 15z^2+23z+4=0 | | n4−2=2 | | 7y-3(y-2)=6(y+1) | | 3/7=y/10 | | 5x+5=-1+x | | 4(3x-9)=-10 | | -1/2(2x-4)=-12 | | n/4−2=2 | | 3(2x+1)+2=1/5-x | | (x-104)=0 | | w/2+5=7 | | w/2+ 5=7 | | 6x+6=3(11-x) | | 7u+8=99 |